Evaluation of Corrosion in Reinforced Concrete: A Review on the Application of UPV Method - Othman, Fatin Zulaikha; Ayop, Sallehuddin Shah (Recent Trends in Civil Engineering and Built Environment, 2021)
Corrosion can be considered as one of the problems that threatens the performance of reinforced concrete structures. Corrosion of reinforced concrete steel may leads to concrete cracking that eventually will affects the bearing capacity of concrete members. Non-destructive tests (NDT) are frequently used method in monitoring corrosion of reinforced concrete. This study is conducted to analyse the capability of UPV method as corrosion detection of reinforced concrete. The aims of this study is to review and analyse the behavior of corrosion expansion of reinforcement steel that undergo accelerated corrosion test by using UPV method and to analyse the effect of corrosion products on concrete-steel interface by examining the corrosion crack and the weight loss of reinforcement steel. The utilization of UPV method from previous researches were collected in this study to review the application of this method in detecting corrosion by analyzing the results of UPV reading obtained from previous researches. Weight loss of reinforcement steel also were studied to evaluate the effect of corrosion towards the condition of reinforced concrete. Analysis from the previous findings showed that the UPV readings recorded a reduction in values as corrosion time increases with cracking appeared on the concrete surface and reinforcement steel showed an increase in weight loss at the end of accelerated corrosion test. Hence, from this study, it was able to validate the reliability of UPV method to be adopted as one of the alternative method to evaluate corrosion of reinforced concrete.